2015
DOI: 10.1016/j.rhm.2015.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Sexual torture of Palestinian men by Israeli authorities

Abstract: In the context of the Israeli-Palestinian conflict, arrests and imprisonment of Palestinian men in their early adulthood are common practice. The Public Committee Against Torture in Israel (PCATI) collected thousands of testimonies of Palestinian men allegedly tortured or ill-treated by Israeli authorities. There are many types of torture, sexual torture being one of them. This study is based on the PCATI database during 2005-2012, which contains 60 cases-- 4% of all files in this period--with testimonies of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 27 publications
0
33
0
Order By: Relevance
“…These children suffer physical injuries, a variety of somatic complaints, enuresis, constipation, sleep disorders, and psychological disorders. [4756] A follow-up study on children who were tortured or whose parents were tortured in Chile found that both the prevalence and frequency of somatic symptoms increased over time after resettlement in Denmark. [55]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These children suffer physical injuries, a variety of somatic complaints, enuresis, constipation, sleep disorders, and psychological disorders. [4756] A follow-up study on children who were tortured or whose parents were tortured in Chile found that both the prevalence and frequency of somatic symptoms increased over time after resettlement in Denmark. [55]…”
Section: Resultsmentioning
confidence: 99%
“…The witnessing, experience, and perpetration of sexual violence and sexual exploitation are documented by numerous papers in this review, nine of which dealt exclusively with these issues. [56, 100, 104, 105, 115119] All included studies of children associated with armed groups document sexual violence of and by these children. However, the studies that focus exclusively on sexual violence and exploitation, suggest the problem is far more widespread.…”
Section: Resultsmentioning
confidence: 99%
“…Although electric torture to genitals has been previously described (i.e. Iran Human Rights Documentation Center, 2011; Weishut, 2015), no known research exists that investigates the sequelae and optimum rehabilitation procedures for patients presenting with ure-thral sequelae. This paper aims to help address this gap with two objectives:…”
Section: S H O R T S C I E N T I F I C R E P O R Tmentioning
confidence: 99%
“…For many women, especially in societies where honor is relevant to selfconcept, rape constitutes an eclipse (see Cahill, 2001) or possible loss of inner self as linked to gendered ideals of purity and the socially imposed mandate to defend collective honor. For men among whom socially constructed ideas of what it means to be a man means being heterosexual, sexual torture is often associated with a fear of having become homosexual, in other words, of being degraded to not being a true man any more (Carpenter, 2006;Sivakumaran, 2007;Weishut, 2015). In certain contexts, for men for whom honor is dependent on the sexual purity of his wife, a man can likewise be degraded through his manhood by being subjected to the genderized torture of witnessing the rape of his wife.…”
Section: The Legal Contoursmentioning
confidence: 99%